Examining Outcome-Based Education on Civic Disposition and Civic Skills among Civic Education Students at Mulawarman University - Siti Nur Aisyah Afni Dujani; Nur Fitri Handayani; Jawatir Pardosi; Wingkolatin; Suryaningsi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
Outcome-Based Education (OBE) is a student-centered pedagogical approach that emphasizes achieving predetermined learning outcomes through active, participatory, and meaningful learning experiences. Although OBE has been widely adopted in higher education, empirical evidence regarding its relationship with the development of students’ civic disposition and civic skills—particularly within the Indonesian context—remains limited. This study aims to examine the effect of OBE implementation on the civic disposition and civic skills of undergraduate students in the Pancasila and Civic Education Study Program at Mulawarman University. Using a quantitative approach with an explanatory survey design, the study involved 76 students selected through purposive sampling who had experienced an OBE-based curriculum. Data were collected via a four-point Likert-scale questionnaire, tested for validity and reliability, and analyzed using simple linear regression. The findings revealed that OBE implementation has a positive and significant relationship with both civic disposition(β = 0.656, p < 0.001), accounting for 43.0% of the variance, and civic skills (β = 0.624, p < 0.001), accounting for 39.0% of the variance. These results indicate that OBE implementation is associated not only with academic achievement but also with the cultivation of essential civic traits and competencies. This study contributes to the field of civic education by extending the discourse on OBE beyond academic performance, highlighting its relevance in fostering active citizenship. Consequently, these findings may serve as a reference for educators and curriculum developers seeking to strengthen the role of higher education in preparing students for democratic and social engagement.